Efficient agmatine production using an arginine decarboxylase with substrate‐specific activity. Issue 9 (28th March 2017) - Sun, Anran; Song, Wei; Qiao, Weihua; Chen, Xiulai; Liu, Jia; Luo, Qiuling; Liu, Liming
Abstract: BACKGROUND: Agmatine is a valuable pharmaceutical intermediate biosynthesised froml ‐arginine by arginine decarboxylase (EC 4.1.1.19). It has various potential therapeutic functions in neurotransmitter systems, nitric oxide synthesis, and polyamine metabolism. To establish a green and efficient process for agmatine production, a novel arginine decarboxylase ( Sp A9) from Shewanella putrefaciens was identified, overexpressed, and functionally characterised in this study. RESULTS: The Sp A9 gene from S. putrefaciens was overexpressed in Escherichia coli BL21(DE3), and the recombinant Sp A9 was purified 7.7‐fold. The recombinant Sp A9 exhibited a higher K cat / K m value (4.8 s −1 mM −1 ). Furthermore, Sp A9 showed the highest activity at pH 8.5 and 37°C towardsl ‐arginine. The highest enzyme activity of 1281 U mL −1 was achieved by optimising the nutrient, culture, and induction conditions. Under optimum transformation conditions, the maximum conversion yield of agmatine was 92.6%, with a space‐time yield of 276.88 g L −1 ·day −1 at a 1 L scale. CONCLUSIONS: To our best knowledge, this bioprocess produced the highest yield and conversion rate of any biocatalyst method reported yet. It is also a greener and more cost‐effective method for agmatine production compared with other available methods in the pharmaceutical industry. © 2017 Society of Chemical Industry